1990
DOI: 10.1111/j.1365-2672.1990.tb02565.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival strategy of Escherichia coli and Enterococcus faecalis in illuminated fresh and marine systems

Abstract: Some effects of visible light on Escherichia coli and Enterococcus faecalis in natural freshwater and seawater were studied by plate counts, colony area measurements, and direct counts. A large number of somnicells (non-culturable cells) were noted in illuminated systems as compared with non-illuminated ones. Colony areas were significantly smaller in illuminated systems. Indirect activity measurements were used to test the effects of visible light on the ability of E. coli and Ent. faecalis to metabolize subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 37 publications
1
58
2
Order By: Relevance
“…However, some studies have demonstrated that VBNC cells retain some pathogenic effects [23][24][25]. Some authors have shown that E. coli VBNC cells retain their pathogenicity by keeping the ability to produce enterotoxin [3,23], or by preserving plasmids involved in pathogenicity [9]. Oliver and Bockian [22] showed that injecting Vibrio vulnificus VBNC cells in mice killed the animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have demonstrated that VBNC cells retain some pathogenic effects [23][24][25]. Some authors have shown that E. coli VBNC cells retain their pathogenicity by keeping the ability to produce enterotoxin [3,23], or by preserving plasmids involved in pathogenicity [9]. Oliver and Bockian [22] showed that injecting Vibrio vulnificus VBNC cells in mice killed the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Oliver and Bockian [36] observed a lethal effect in mice inoculated with VBNC cells of Vibrio vulnificus. Other works established that Escherichia coli VBNC cells kept their pathogenicity by keeping the ability to produce little amounts of enterotoxin [2,37] or by preserving plasmids involved in pathogenicity [9]. Chaiyanan et al showed conservation of cholera toxin and toxinassociated genes in VBNC cells of Vibrio cholerae [13].…”
Section: Discussionmentioning
confidence: 99%
“…In freshwaters however, the survival of salmonellae may be extended for periods longer than in seawater, as a result of the presence of humic materials that may absrobe U. V. radiation, therefore, protecting the cells from possible damage to the DNA by radiation (Davies & Evison, 1991). Generally, natural light affects the uptake of nutrients and inhibits active transport and biosynthesis in Escherichia coli (Barcina et al, 1990); its effect on salmonellae serovars may require further investigation (Sinton et al, 2007).…”
Section: Survival In Naturementioning
confidence: 99%